Smooth moves - Harte, Marie (Harte, Marie. Veteran movers., 2019)
Former Marine Cash Griffith is a brawny beacon for trouble, always finishing a fight that someone else starts. Working at his family's moving company, he does his best to keep a low profile, but he can't help but tangle with the newest employee, Jordan Fleming. When Jordan joins Vets on the Go! she has her hands full with her new job and her rebellious teenage brother, not to mention going toe to toe with the obnoxious, arrogant, incredibly hot Marine at work. Soon their battles turn to camaraderie, and one kiss leads to a connection neither of them expected. But when dark secrets come to light, will their bond break...or strengthen into a happily-ever-after they desperately desire?